Podatek rolny w dochodach budżetowych gmin - Chmielewska, Marzena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
The aim of elaboration was an assessment of farming tax revenues of the community’s budgets. The article presents relations between discussed revenues and chosen elements of the community’s budgets (own revenues and other taxes: including property tax, agricultural tax, forest tax, and tax on means of transport). The participation of cash inflow from farming tax in communities budgets were not differentiated, depending on kind of communities. Trends in chosen ratios in all communities (villages and other) were in general similar.